The Effect of Work Environment and Leadership Style on Employee Performance at the Ulumusi Sub-District Office, Empat Lawang Regency - Eka Irawati; Yun Fitriano; Yudi Irawan (Penerbit Jurnal Indonesia, 2023)
Human resource managers are required to have a leader where he can work together and can suppress possible conflicts that will occur in the work group so as to achieve the organizational goals of the agency. In addition, the work environment is of course also related to employee performance with the conditions that exist around an agency that is related. The purpose of this study was to determine the effect of work environment and leadership style on employee performance at the Ulu Musi Sub-District Office, Empat Lawang Regency. The sample in this study was 36 employees at the Ulu Musi Sub-District Office, Empat Lawang Regency. Data collection using questionnaires and the analysis method used is multiple linear regression, determination test and hypothesis testing. The results showed the regression value Y = 3.195 + 0.323X1 + 0.618X2 +e. The work environment has a significant effect on employee performance at the Ulu Musi Sub-District Office, Empat Lawang Regency, because the significant value of 0.031 is less than 0.05. Leadership style has a significant effect on employee performance at the Ulu Musi Sub-District Office, Empat Lawang Regency, because the significant value of 0.000 is less than 0.05. The work environment and leadership style have a significant effect together on employee performance at the Ulu Musi Sub-District Office, Empat Lawang Regency because the significant value of 0.000 is less than 0.05, thus the initial hypothesis proposed is proven (Ha accepted). That is, there is a significant influence between the work environment and leadership style on performance together. The coefficient of determination of R square is 0.636. This means that the work environment and leadership style affect performance by 63.6% while the rest (100-63.6% = 36.4%) is influenced by other causal factors not examined in this study.